Valores humanos, qualidade de vida no trabalho e competências profissionais: proposição de modelo integrativo e estudo com jovens trabalhadores - Michelle Regina Santana Dutra (2023)
The present thesis aimed to analyze the relationships between human values, quality of work life (QWL), and professional competencies in the perception of young Brazilian workers, residing in all five federative regions and affiliated with the same vocational institution that complies with the Apprenticeship Law. The specific objectives were to revalidate the scales of the constructs involved, describe each dimension after revalidation, and validate an integrative model in the perception of young workers. The target population was chosen due to their idiosyncrasies, as they belong to a more vulnerable group facing greater difficulties in entering and remaining in the labor market. To achieve this, a descriptive and explanatory research was conducted, using a quantitative approach. The theoretical models adopted to guide the construction of the integrative model were Schwartz (1992) for human values, Ferreira (2011) for QWL, and Paiva (2007) for professional competencies, using the respective scales: PVQ-R by Torres, Schwartz, and Nascimento (2016); IA_QWL by Ferreira (2011); and ECP by Paiva, Rocha, and Fujihara (2018). Exploratory research aims to identify causal relationships, which allows for a better understanding of behaviors and reflection on the need for improvements in the formative process of young workers, both in the educational environment and in the organizations they work for. A total of 3,232 valid questionnaires were obtained and processed for exploratory factor analyses (EFAs). All scales were revalidated through EFAs. Additionally, the descriptive data of the dimensions were presented after the revalidations, indicating all the changes that occurred. Causal relationships were tested using structural equation modeling, which confirmed the hypotheses and the thesis argument proposed in the introduction of this work, albeit with direct positive and negative relationships in each construct. This study contributes to the understanding of the behavior of this workforce and has significant managerial implications. It can guide organizations in developing effective learning programs for the professional development of these young individuals, aiming for their future integration into the labor market. The study also identified research limitations and suggests directions for future investigations.